Pengaruh Penambahan Fermentasi Dedak Padi pada Ransum Terhadap Performan Domba - Diah Reni Asih; Miftahuddin Ahmad; Rohmatul Anwar; Dwi Subakti Prastiyo (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
The purpose of this study was to determine the performance of sheep with the addition of fermented rice bran in the ration. This research was conducted in August-October 2023 at the sheep farm in Putra Buyut Village, Gunung Sugih District, Central Lampung Regency. In this study, 12 sheep were used with the age of 2 years and body weight of 20-23 kg. This study uses fermented rice bran as an addition to sheep rations, the addition in the ration with different percentages, namely P0 (forage feed without the addition of fermented rice bran), P1 (forage feed with the addition of 10% fermented rice bran), P2 (forage feed with the addition of 15% fermented rice bran), P3 (forage feed with the addition of 20% fermented rice bran). This study used a complete randomized design (CRD) with 4 treatments and 3 replicates. Parameters observed in this study were feed consumption, body weight gain and feed conversion. The results of this study showed that the provision of fermented rice bran in the ration had no significant effect (P>0.55) on feed consumption, body weight gain, and feed conversion. The highest average weight gain was in P0 (150.67).